EFFECT OF HUMOR LEADERSHIP ON INVENTIVENESS OF EMPLOYEES AND ADMINISTRATIVE RELIABILITY. EMOTIONAL INTELLIGENCE'S MODERATING IMPACT - Arshad Ali; Ahmad Tisman Pasha; Shaukat Malik (International Journal of Multidisciplinary Sciences and Arts, 2022)
The purpose of this research is to examine how humor leadership styles affect innovation and productivity in Pakistan's mobile telecommunications industry in the south Punjab area. It examines how emotional intelligence may be used by leaders to boost organisational performance. This research demonstrates the impact that emotional intelligence has on innovation and productivity in the telecommunications industry in this area. This research uses information from a highly regarded mobile telecommunications industry in the South Punjab area of Pakistan. This article explores a variety of perspectives on leadership. In various settings, these theories argue, leaders act in certain ways. For them, the ultimate success of their businesses depends on continuing the current trend of development and productivity. This research also discusses the many leadership styles used by successful business owners and managers to foster an environment where innovation and productivity thrive. The information for this research was gathered by use of questionnaires. The study's statistical analysis and findings corroborate the link between hilarious leadership and employee innovation, which in turn boosts organisational effectiveness. Humorous leadership is seen to have a beneficial influence on employees' ability to think beyond the box. A leader should keep the office lighthearted to foster an environment conducive to innovation. KEYWORDS: Organizational effectiveness, emotional acuity, self-defeating humour, self-enhancing comedy, mobile communications, and staff creativity are all boosted by humour that fosters social connections and competition.